Mind Nursing Intervention for Improving Coping Mechanisms among Mother with Preeclampsia: A Quasy-Experimental Study - Yenny Puspitasari; Zainal Andy Saputra; Suci Anggraini (Journal Of Nursing Practice, 2025)
Background: Preeclampsia is one of the complications of pregnancy with the highest morbidity and mortality rates. This condition often triggers women with preeclampsia who must undergo conservative therapy to feel stressed, anxious, and traumatized. This will make the coping mechanisms of mothers with preeclampsia become maladaptive. Objective: This study aims to examine the effectiveness of mind intervention (consist of guided imagery and progressive muscle relaxation) for improving the coping mechanisms of mothers with preeclampsia. Methods: A quasi-experimental study with pre and post-test was perform among 60 ofpreeclampsia mother (30 of control and 30 of intervention groups). The control groups were given standard therapy, while the intervention groups were given standard therapy and three sessions of mind intervention. Data on coping mechanisms were measured and analyzed using Wilcoxon and Mann-Whitney test to evaluate the effectiveness of the intervention. Results: The results showed that before the intervention, there was no significant difference in coping mechanisms between the control (Mean±SD: 76,93±19,285) and treatment groups (Mean±SD: 75,47±19,541). However, after the intervention, a significant difference was observed, with the control group scoring (Mean±SD: 79,93±19,285) and the treatment group scoring (Mean±SD: 92,47±19,541), and a p-value = 0.035. Conclusion: Mind’s intervention is effective for improving the coping mechanisms of preeclampsia mothers. Therefore, it can be recommended as a complementary nursing care approach to enhance psychological resilience and promote better outcomes in managing preeclampsia.